Motor control strategies during unpredictable force control tasks in humans. (16th July 2020) - Almotairy, Nabeel; Kumar, Abhishek; Grigoriadis, Anastasios
Abstract: Background: There are fundamental similarities and differences between the jaw and hand motor systems. However, it is unclear how the two systems respond to unpredictable task demands. Objective: To investigate and compare the force control of the jaw motor system (OMS) and the hand motor system (HMS) during unpredictable load changes. Methods: Seventeen healthy adults (24.0 ± 4.3 years) performed two standardised force control tasks (OMS and HMS). During the OMS, the participants asked to bite and pull a force transducer with the front teeth. While during HMS they pinched and pulled the same force transducer with their index and thumb fingers. Series of loads were added to a string attached to the transducer in an unpredictable (sequential and non‐sequential) manner. The entire force profile during the task was divided into "initial" and "latter" segments. The force control was analysed and compared between the OMS and HMS in terms of peak force during the initial segment and holding force and force variability during the latter segment. Results: The peak force, holding force and force variability were higher for the OMS than the HMS ( P  < .001). However, there were no differences in the peak force, holding force or force variability between the sequential and non‐sequential load changes ( P  > .05). Conclusions: The results showed that unpredictable load changes did not affect the force control during the motor control task. This study suggests that both the motor systems are optimised in performing simple motor control tasks and are rather resilient to motor unpredictability.